2009
DOI: 10.2310/7750.2008.08019
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Survey regarding Perioperative Antiseptic Practices

Abstract: Many traditional perioperative antiseptic techniques are not being performed by respondents. Calculated infection rates are very low for all queried procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Our study did not query why respondents chose their answers. Given that fewer than 25% of Mohs fellowship–trained dermatologists and even fewer other dermatologists perform liposuction or hair transplants, the polled physicians may simply not have been exposed to enough dermatologists who perform these procedures …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study did not query why respondents chose their answers. Given that fewer than 25% of Mohs fellowship–trained dermatologists and even fewer other dermatologists perform liposuction or hair transplants, the polled physicians may simply not have been exposed to enough dermatologists who perform these procedures …”
Section: Discussionmentioning
confidence: 99%
“…Given that fewer than 25% of Mohs fellowship-trained dermatologists and even fewer other dermatologists perform liposuction or hair transplants, the polled physicians may simply not have been exposed to enough dermatologists who perform these procedures. 11 PCPs also identified dermatologists with fellowship training in MMS as the best specialists to perform MMS, with women and U.S. medical school graduates being the most likely to have a preference for Mohs fellowship-trained dermatologists. Although it is not clear why one sex may have a greater inclination for a dermatologist with fellowship training to perform MMS, the inclusion of dermatology in medical school teaching and greater exposure to dermatologic surgeons may be more commonplace in U.S. medical schools than foreign medical graduates.…”
Section: Discussionmentioning
confidence: 99%
“…A survey regarding perioperative antiseptic practices among members of the American College of Mohs Surgery showed that many traditional aseptic techniques are not used among dermatologists. For example, only 35% of respondents reported utilizing a preoperative hand scrub before Mohs Surgery [6].…”
Section: The Dermatology Office Environmentmentioning
confidence: 99%
“…8 This article will explore the presumed advantages and shortcomings of each individual garb in detail (Table I). Other reasons for wearing surgical garb such as universal precautions, regulations, or societal expectations are beyond the scope of this article.…”
mentioning
confidence: 99%